2001
DOI: 10.1111/1469-7610.00788
|View full text |Cite
|
Sign up to set email alerts
|

Using Parental Ratings to Study the Etiology of 3‐year‐old Twins’ Problem Behaviors: Different Views or Rater Bias?

Abstract: Child Behavior Checklist questionnaires (Achenbach, 1992), filled in separately by mothers and fathers, were collected for an effective sample of 3501 Dutch 3-year-old twin pairs. To disentangle the child's phenotype from that of the rater, two contrasting models were fitted to the data. One model, called a Rater Bias model, is based on the assumption that both parents assess exactly the same behaviors in the child. A weaker alternative of this model, called a Psychometric model, assumes that apart from these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
63
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 40 publications
11
63
1
2
Order By: Relevance
“…The genetic influences on the variance of the raterspecific parts are higher for the father reports in the analyses. Previous studies of internalizing and externalizing disorders in young twins usually found these estimates to be larger in maternal ratings (Bartels et al, 2003;Bartels et al, 2004a;Boomsma et al, 2005;Van der Valk et al, 2001;Van der Valk et al, 2003). This may support the notion that that there are sex differences in the perception of parents with respect to this phenotype in their children and that fathers may add important extra information regarding the thought problems phenotype.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The genetic influences on the variance of the raterspecific parts are higher for the father reports in the analyses. Previous studies of internalizing and externalizing disorders in young twins usually found these estimates to be larger in maternal ratings (Bartels et al, 2003;Bartels et al, 2004a;Boomsma et al, 2005;Van der Valk et al, 2001;Van der Valk et al, 2003). This may support the notion that that there are sex differences in the perception of parents with respect to this phenotype in their children and that fathers may add important extra information regarding the thought problems phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Hewitt et al, (1992) studied internalizing behavior in prepubertal (8-11 years) and pubertal twins (12-16 years), and found evidence for such genetic effects. Dutch twin studies on internalizing and externalizing behaviors also found that the unique viewpoint of parents does not solely reflect rater bias (Bartels et al, 2003;Bartels et al, 2004a;Bartels et al, 2007;Van der Valk et al, 2001;Van der Valk et al, 2003).…”
mentioning
confidence: 99%
“…When results of the Rutter-A and -B scales or from the parent or teacher rated DBRS were compared (Table 1), teacher ratings often resulted in lower heritability estimates (around 50%) than parent ratings and additionally described shared and non-shared environmental effects [41,67,97,99,106]. Besides possible measurement error, findings imply that parents and teachers might rate different ADHD behavior, which has explicitly been shown for differences in the ratings of mothers and fathers [43,113]. It therefore, was suggested to combine information from parents and teacher ratings to diagnose a genetically more clearly determined subtype, as combined ratings showed an additive genetic effect of 79% in two independent studies using items of the Rutter-A and -B scales [97,106].…”
Section: Rater Effectsmentioning
confidence: 94%
“…Analyses of the Child Behavior Checklist (CBCL; Achenbach, 1992) indicated that at age 3, genetic factors explain at least 50% of the variance on the two broadband scales of Externalizing and Internalizing. Shared environmental influences were significant but more modest, explaining no more than a third of the variance for Externalizing and roughly 10% of the variance for Internalizing behaviors (Bartels et al, 2004;van den Oord, Verhulst, & Boomsma, 1996;van der Valk, van den Oord, Verhulst, & Boomsma, 2001). All CBCL problem syndromes were significantly heritable at age 3 years; however, the pattern of genetic and environmental effects was variable.…”
mentioning
confidence: 93%